The Teacher’s Strategies in Teaching Reading: A Classroom Observation Research at the Eleventh Grade of MA N Purworejo in the Academic Year of 2016/2017 - Reyval Galih Trisnawan; Tusino Tusino (Scripta : English Department Journal, 2019)
The objective of this research is to describe whether are the strategy in teachingreading at eleventh grade students of MA N Purworejo in academic year 2016/2017. Inthis research, the researcher took 2 teachers as the subject of the research. In the ofobservation research, the research tried to analyze the teacher’s teaching strategy inreading conducted by the teacher in the classroom to find out whether strategies wereused or not by the teacher.The population of this research is the English teacher at MA N Purworejo. Thesample of this research is the English teachers of eleventh grade student at MA NPurworejo. This is qualitative research, because the purpose is to get a picture andinformation about the strategies used in the English language teacher especially aboutreading skills. The writer uses two instruments, there are observation and interview. Theobservation to get the data by closely watching and noticing classroom events and theinterview to support the observation, because the interview is a dialogue conducted byinformation to get information from interviewed.The researcher concluded: Teacher teach in IPS class. Teacher use three types,there are guessing, scan the text and analyze vocabulary. Teacher combine threestrategies to teach in the classroom. Strategy often used is drilling and chants. Teacheruse type because many students are often difficult. Their vocabulary is limited.Therefore the teacher uses this method for imitating and repeating word. Example : Thestudents repeated teacher after said the vocabulary. The teacher says one word andmeaning then the student repeated that word. Teacher teach in IPS class. Teacher usethree types, there are guessing, scan the text and analyze vocabulary. Teacher combinesthree strategies to teach in the classroom. Strategy often used is scan the text. Teacheruse this strategy because to improve the vocabulary. Their pronunciation are low, somake the student difficult to find the meaning of the text .Therefore the teacher use thismethod to make the student improve their vocabulary. Example: teacher give text to thestudent and the student find the meaning of the text and translate to Indonesian word.